Carol Shields and Simone de Beauvoir: Immanence, Transcendence, and Women’s Work in A Fairly Conventional Woman, The Stone Diaries, and Unless - Guenther, Bethany (Studies in Canadian Literature, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Many of the female protagonists in Carol Shields’s fiction are defined by the daily slog of their domestic work, ostensibly doomed to what Simone de Beauvoir famously called “immanence.” However, Shields does not view women’s domestic work with the same terror as de Beauvoir. Shields equips the female protagonists in A Fairly Conventional Woman (1982), The Stone Diaries (1993), and Unless (2002) with some sort of artistic or creative work that allows them the “expansion of existence,” or transcendence, that de Beauvoir saw as only possible for men. Considering Shields’s fiction in light of de Beauvoir’s theories not only illuminates Shields’s own feminist philosophy but also situates her in the larger feminist community by demonstrating that she does indeed use a feminist approach to her recognition of women’s work as a potential (and necessary) source of transcendence.